2015
DOI: 10.3382/ps/pev278
|View full text |Cite
|
Sign up to set email alerts
|

Presence of pathogenicity islands and virulence genes of extraintestinal pathogenic Escherichia coli (ExPEC) in isolates from avian organic fertilizer

Abstract: Poultry litter is commonly used as fertilizer in agriculture. However, this poultry litter must be processed prior to use, since poultry have a large number of pathogenic microorganisms. The aims of this study were to isolate and genotypically and phenotypically characterize Escherichia coli from avian organic fertilizer. Sixty-four E. coli isolates were identified from avian organic fertilizer and characterized for ExPEC virulence factors, pathogenicity islands, phylogenetic groups, antimicrobial resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
3
8
1
2
Order By: Relevance
“…Regarding beta-lactams, ampicillin resistance frequency varies from around 20% [58] to over 80% [59], reaching 100% in clinical isolates [60,61]. Similar data have been described for first-generation cephalosporins [62,63], while low resistance has been reported to second and third-generation cephalosporins [64], except for ceftiofur, despite reports of low resistance frequencies in some collections [62,65].…”
Section: E Colisupporting
confidence: 57%
“…Regarding beta-lactams, ampicillin resistance frequency varies from around 20% [58] to over 80% [59], reaching 100% in clinical isolates [60,61]. Similar data have been described for first-generation cephalosporins [62,63], while low resistance has been reported to second and third-generation cephalosporins [64], except for ceftiofur, despite reports of low resistance frequencies in some collections [62,65].…”
Section: E Colisupporting
confidence: 57%
“…These results exemplify the potential of APEC as a zoonotic pathogen for humans, combined with the knowledge that APEC can colonize the GI tract of poultry (69). island (72). Of all the isolates tested, 50% of them were resistant to at least one antibiotic, with the most common ones being tetracycline, amoxicillin, ampicillin, and streptomycin.…”
Section: Zoonotic Potential Of Apecsupporting
confidence: 56%
“…Additional evidence for APEC and the colicin plasmids as a public health concern is seen in the identification of a plasmid in a Salmonella serovar and drug resistant E. coli isolates in avian organic fertilizer(70)(71)(72). Salmonella enterica serovar Kentucky is a pathogen that has been increasingly identified as a causative agent of disease in poultry, humans, and companion animals; further, it has recently been found to carry the conserved pathogenicity island of the ColV plasmid(70,71).…”
mentioning
confidence: 99%
“…Studies about virulence genes in bacteria isolated from feed were not found in the literature, indicating that our work is the first report. Other studies evaluating the presence of genes related to APEC, DEC and ETEC were found for poultry with colibacillosis lesions and healthy animal feces (Jianguo et al, 2012), marketed chicken carcasses (Koga et al, 2015), in aviaries (Carvalho et al, 2015) and in organic fertilizers resulting from chicken manure composting (Gazal et al, 2015). The occurrence of the five gene predictors for APEC was verified in almost all studies.…”
Section: Resultsmentioning
confidence: 80%
“…The study of Torres et al (2011) attributed the contamination of feed to cooling after pellet process, storage and transportation. Other authors demonstrated the tolerance to adverse conditions of E. coli to survive in dry environments, such as dried corn (Dargatz et al, 2005), and organic fertilizer after the composting manure process (Gazal et al, 2015).…”
Section: Resultsmentioning
confidence: 99%